Long-term trends in the consumption of sugary and diet soft drinks among adolescents: a cross-national survey in 21 European countries - Chatelan, Angeline; Lebacq, Thérésa; Rouche, Manon; Kelly, Colette; Fismen, Anne-Siri; Kalman, Michal; Dzielska, Anna; Castetbon, Katia (European journal of nutrition, 2022)
PURPOSE: To assess country-level trends in the prevalence of daily consumption of sugary (2002-2018) and diet (2006-2018) soft drinks among European adolescents, overall and by family material affluence. METHODS: We used 2002, 2006, 2010, 2014 and 2018 data from the 'Health Behaviour in School-aged Children' survey. Nationally representative samples of adolescents completed a standardised questionnaire at school, including a short food frequency questionnaire (n = 530,976 and 21 countries for sugary soft drinks; n = 61,487 and 4 countries for diet soft drinks). We classified adolescents into three socioeconomic categories for each country and survey year, using the Family Affluence Scale. Multilevel logistic models estimated time trends, by country. RESULTS: Sugary soft drinks: the prevalence of daily consumption (≥ 1×/day) declined in 21/21 countries (Plinear trends ≤ 0.002). Absolute [range - 31.7 to - 3.4% points] and relative [range - 84.8 to - 22.3%] reductions varied considerably across countries, with the largest declines in Ireland, England and Norway. In 3/21 countries, the prevalence of daily consumption decreased more strongly in the most affluent adolescents than in the least affluent ones (P ≤ 0.002). Daily consumption was more prevalent among the least affluent adolescents in 11/21 countries in 2018 (P ≤ 0.002). Diet soft drinks: overall, daily consumption decreased over time in 4/4 countries (Plinear trends ≤ 0.002), more largely among the most affluent adolescents in 1/4 country (P ≤ 0.002). CONCLUSIONS: Daily consumption of sugary and diet soft drinks in European adolescents decreased between 2002 (2006 for diet drinks) and 2018. Public health interventions should continue discouraging daily soft drink consumption, particularly among adolescents from lower socioeconomic groups.
Keywords: průzkumy a dotazníky; Artificially sweetened beverages; Socioeconomic inequalities in health; dítě; Sugary soft drinks; Surveys and Questionnaires; Adolescent; lidé; cukry; Sodas; Carbonated Beverages; Artificially Sweetened Beverages; Sugar-sweetened beverages; sycené nápoje; dieta; Diet; Child; Sugars; nápoje slazené umělými sladidly; Trend analysis; Diet soft drinks; Adolescents; mladiství; Health Behaviour in School-aged Children study; Humans